A Representation of SDGs: Payments for Forest Environmental Services (PFES) in Loc Tien Commune, Phu Loc District, Thua Thien Hue Province - Mai Thi Khanh Van (Kelompok Studi Mahasiswa Pengkaji Masalah Internasional Unpar, 2020)
In Vietnam, the policy on payment for forest environmental services (PFES) has been present for a long time, in the orientation of socialization of national forest protection. The role of this policy was not limited to the objective of environmental protection, the overarching objective of PFES has always been the link to develop the sector of environment, economy, and society. This has also been one of the targets of Goal 11: